Modelling the impact of hunting on the coexistence of congeneric deer species in Central Amazonia. (4th April 2022) - de Pinho, F. F.; Lemos, L. P.; Montanarin, A.; El Bizri, H. R.; Santos, J.; Rabelo, R. M.; Valsecchi, J.; Ramalho, E. E.; Paglia, A. P.
Abstract: The long‐term coexistence of sympatric species is dependent on segregation in at least one of three niche dimensions: space, time or feeding habits. Hunting by people can influence species' temporal and spatial patterns and consequently affect their coexistence. We tested the hypothesis that hunting influences spatial and temporal patterns of coexistence of two sympatric deer species ( Mazama americana and Mazama nemorivaga ) in central Amazonia. We described deer hunting patterns using data from an 18‐year community‐based hunting monitoring program and predicted the spatial distribution of deer hunting trips. We used camera traps to (1) estimate the habitat use patterns of each species through conditional occupancy, (2) evaluate whether these species interact and (3) assess how modelled hunting intensity affects deer habitat occupancy. We also tested the temporal overlap of activity time between both species and hunters. We did not find evidence of hunting effects on occupancy and interaction, nor of spatial segregation among the deer species. M. americana was primarily nocturnal and M. nemorivaga primarily diurnal. The overlap between species' temporal activities was relatively low, suggesting temporal niche segregation between species. Hunting activity was mainly diurnal and overlapped with M. nemorivaga active hours. However, we found that M. americana was more frequently hunted than M. nemorivaga . The probability of daytime activity was not influenced by hunting intensity. Temporal segregation, with asynchrony of activity periods, seems to be the mechanism behind the coexistence of M. americana and M. nemorivaga in Central Amazonia. The absence of hunting effects on brocket deer species in our study area suggests a low impact of harvest on both species' behaviour. This indicates that contexts of low human density and large extensions of pristine forests can enable hunted brocket deer populations to be sustained through source‐sink dynamics. Abstract : Hunting can influence species' temporal and spatial patterns of habitat use and consequently affect their coexistence. We used a combination of camera trapping and a hunting monitoring program to investigate the coexistence patterns of two sympatric brocket deer species in central Amazonia, and assess how hunting affects these patterns. The overlap between the species' temporal activities was low, suggesting temporal niche segregation between them. We found no evidence of hunting effects on occupancy and interaction, nor on spatial segregation between the deer species. The absence of hunting effects on brocket deer in our study area suggests a low impact of harvest on both species' behavior.